Reduced Neural Specialization for Word-level Linguistic Prosody in Children with Autism. - Yu, Luodi; Huang, Dan; Wang, Suiping; Zhang, Yang (Journal of Autism & Developmental Disorders, 2023)
Children with autism often show atypical brain lateralization for speech and language processing, however, it is unclear what linguistic component contributes to this phenomenon. Here we measured event-related potential (ERP) responses in 21 school-age autistic children and 25 age-matched neurotypical (NT) peers during listening to word-level prosodic stimuli. We found that both groups displayed larger late negative response (LNR) amplitude to native prosody than to nonnative prosody; however, unlike the NT group exhibiting left-lateralized LNR distinction of prosodic phonology, the autism group showed no evidence of LNR lateralization. Moreover, in both groups, the LNR effects were only present for prosodic phonology but not for phoneme-free prosodic acoustics. These results extended the findings of inadequate neural specialization for language in autism to sub-lexical prosodic structures.